Incidence of patella baja following patellar eversion in total knee arthroplasty - Singh, Chander Mohan; Pande, Hrishikesh; Padhi, Prashant Pratim; Prabhakara, Anjan; Philip, Vivek Mathew; Sharma, Yogesh (International Journal of Research in Orthopaedics, 2017)
Background: Patella baja is a rare complication of total knee arthroplasty (TKA) leading to decreased mechanical advantage of the extensor mechanism, decreased knee range of motion, anterior knee pain and increased wear of the tibial and patellar polyethylene. There exists a lack of evidence on whether patellar eversion leads to shortening of the patellar tendon. The present study aims to determine if eversion of patella during TKA leads to patella baja. Methods: Between August 2014 and August 2016, 55 knees undergoing primary TKA with a standard medial parapatellar arthrotomy and eversion of patella were included in this two point cross sectional study. Preoperative X-rays were taken to assess the length of the patellar tendon and Insall Salvati ratio (ISR). Postoperatively the Blackburne Peel Index (BPI), ISR and patellar tendon lengths were assessed on lateral X-rays to look for any incidence of patella baja. Results: The postoperative change in the length of the patellar tendon was unpredictable; though most of them decreased. The pre and post op difference in the length of patellar tendon was statistically significant in females (4.43±0.20 cm vs. 4.35±0.24 cm; p value-0.005). Significant decrease in length of patellar tendon was seen in patients aged 66-70 years (p= 0.024) and patients with BMI >30 kg/m2. No case of true patella baja was found postoperatively. No significant correlation could be established between ISR and age, sex or BMI of the patients. Conclusions: The different risk factors for post TKA shortening of patellar tendon include female gender and higher BMI (>30 Kg/m²). However eversion of patella during TKA may not lead to an increased incidence of true patella baja.